College Students' Perception of State-Managed Debt - Korniawan, Rostamaji (International Journal of Multidisciplinary: Applied Business and Education Research, 2024)
State-managed debt has always been a polemic in every country, including Indonesia. Some people's perceptions did not align with the Government's debt policy, including some college students'students' perceptions. Therefore, this study, which is of significant importance, aims to determine the public's understanding, especially college students, of state-managed debt. The Government values the insights of college students, as their perceptions are crucial in shaping public learning regarding debt management. The research was conducted using a qualitative approach through in-depth interviews with five informants outside Jabodetabek (Jakarta, Bogor, Depok, Tangerang, and Bekasi) in Indonesia. The five informants represent the college student community with different educational backgrounds and genders. Based on the in-depth interviews, the results found that all informants' perceptions described the terminology of state-managed debt sufficiently. Likewise, when they described what the investment was. Despite differences in educational backgrounds, each college student could articulate their perceptions of state-managed debt. The study found that the literature on public finance was still limited. Therefore, this research underscores the potential for growth in public finance literacy among college students, highlighting the crucial and reassuring role of the Government in providing comprehensive lessons and accurate information to the younger generation about the benefits of prudent state-managed debt.